Disability and Sexual Orientation Disclosure on Employment Interview Ratings: An Analogue Study. (July 2018) - Dispenza, Franco; Kumar, Asha; Standish, Jonathan; Norris, Spenser; Procter, Jonathan
This study examined the effects of sexual orientation disclosure, disability type disclosure (physical, psychiatric, no disability disclosed), and an applicant's gender on employment interview ratings. Utilizing an experimental 2 × 2 × 3 analogue research design administered via Internet, a total of 424 undergraduate university students from a Southeast U.S. urban university volunteered to participate in the study. Volunteers were randomly assigned to one of 12 conditions in which a mock applicant's sexual orientation and disability type were not disclosed. Participants reviewed resume and interview transcripts of the applicant they were randomly assigned to, and then rated the applicant's qualifications, work skills, and their own personal comfort with disclosure. Participants were also asked to provide narratives regarding their decision-making process. A factorial MANCOVA revealed a statistically significant interaction effect for sexual orientation disclosure, disability type disclosure, and gender. Findings are discussed, along with limitations, implications for rehabilitation counseling, and implications for future research.